A competing risk survival analysis of the impacts of team formation on goals in professional football - Le Coz, Sebastian; Iapteff, Loic; Rioland, Maxime; Houde, Titouan; Carling, Christopher; Imbach, Frank (Frontiers in Sports and Active Living, 2024)
Introduction This study investigated the influence of team formation on goal-scoring efficiency through analysing the time required for a goal to be scored in elite football matches. Method The analysis was conducted using a comprehensive open access dataset encompassing eight major football competitions, including prestigious events such as the World Cup and the UEFA Champions League. It notably focused on the competing risks framework and employed the Fine and Gray model to account for the interplay between two competing events: team A scoring and team B scoring. Results Through analysis of Team A’s goal occurrences, we assessed the offensive capabilities of its formation and the defensive effectiveness of Team B’s composition in relation to the time it took for Team A to score a goal. Findings revealed that teams employing the 4-3-3 and 4-2-3-1 formations outperformed other formations (3-4-3, 3-5-2, 4-4-2, 4-5-1, 5-3-2, 5-4-1) regarding goal-scoring efficiency. Discussion By shedding light on the impact of team formation on goal scoring, this research contributes to a deeper understanding of some of the successful strategic aspects of elite football.